Genomic Studies in a Large Cohort of Hearing Impaired Italian Patients Revealed Several New Alleles, a Rare Case of Uniparental Disomy (UPD) and the Importance to Search for Copy Number Variations - Morgan, Anna; Lenarduzzi, Stefania; Cappellani, Stefania; Pecile, Vanna; Morgutti, Marcello; Orzan, Eva; Ghiselli, Sara; Ambrosetti, Umberto; Brumat, Marco; Gajendrarao, Poornima; La Bianca, Martina; Faletra, Flavio; et al. (Frontiers in Genetics, 2018)
Hereditary hearing loss (HHL) is a common disorder characterized by a huge genetic heterogeneity. The definition of a correct molecular diagnosis is essential for proper genetic counseling, recurrence risk estimation, and therapeutic options. From 20% to 40% of patients carry mutations in GJB2 gene, thus, in more than half of cases it is necessary to look for causative variants in the other genes so far identified (approximately 100). In this light, the use of next-generation sequencing technologies has proved to be the best solution for mutational screening, even though it is not always conclusive. Here we describe a combined approach, based on targeted re-sequencing (TRS) of 96 HHL genes followed by high-density SNP arrays, aimed at the identification of the molecular causes of non-syndromic HHL (NSHL). This strategy has been applied to study 103 Italian unrelated cases, negative for mutations in GJB2, and led to the characterization of 31% of them (i.e. 37% of familial and 26,3% of sporadic cases). In particular, TRS revealed TECTA and ACTG1 genes as major players in the Italian population. Furthermore, two de novo missense variants in ACTG1 have been identified and investigated through protein modelling and molecular dynamics simulations, confirming their likely pathogenic effect. Among the selected patients analyzed by SNP arrays (negative to TRS, or with a single variant in a recessive gene) a molecular diagnosis was reached in ~36% of cases, highlighting the importance to look for large insertions/deletions. Moreover, copy number variants analysis led to the identification of the first case of uniparental disomy involving LOXHD1 gene. Overall, taking into account the contribution of GJB2, plus the results from TRS and SNP arrays, it was possible to reach a molecular diagnosis in ~51% of NSHL cases. These data proved the usefulness of a combined approach for the analysis of NSHL and for the definition of the epidemiological picture of HHL in the Italian population.